Text appeal : a novel - Roberts, Amber (Alcove Press, 2023)
"As the only woman programmer at her firm, Lark is thrilled to land an account for a huge client. But her dream job quickly becomes a nightmare when she accidentally projects a scandalous (and completely unsolicited) picture from her phone onto the screen during a presentation. Before she can recover, her coworkers jump in to steal the account, leaving Lark jobless and broke. When a friend suggests text message-based sex work as a stopgap between jobs, Lark is dubious. She's all about sex positivity, but carrying out sexual fantasies--even digitally and anonymously--with complete strangers is daunting. How will she explain how she's earning a living--especially to Toby, her good friend and longtime hopeless crush? Still, she needs the money, and after a few (embarrassing and hilarious) false starts, she actually starts to like sexting--especially with one particularly charming and nerdy client who keeps popping up in her DMs. But as Lark and Toby grow closer, she finds herself with a decision to make: tell Toby she's a sex worker--and try to forget the anonymous client who has her struggling to separate work from real feelings--or keep the secrets that are piling up in her inbox." --